High-affinity host–guest chemistry of large-ring cyclodextrins. Issue 32 (26th July 2016) - Assaf, Khaleel I.; Gabel, Detlef; Zimmermann, Wolfgang; Nau, Werner M.
Abstract : Unprecedented affinities for large-ring cyclodextrins have been achieved with purely inorganic guest molecules (dodecaborate cluster anions). Abstract : The host–guest chemistry of large-ring cyclodextrins (LRCDs) has been largely unexplored due to the lack of suitable guest molecules that bind with significant affinities to enable potential applications. Herein, we report their complexation with dodecaborate anions (B12 X12 2− ), a novel class of guest molecules. The binding constants of the inorganic guests (10 4 –10 6 M −1 ) allow their classification as the first tight binders for LRCDs.